ChemInform Abstract: A Green Electrochemical Method for the Synthesis of New N, N′‐Diphenylbenzene‐1, 4‐diamine Derivatives. Issue 34 (August 2015) - Nematollahi, Davood; Mahdinia, Saeideh; Karimi, Peiman; Salehzadeh, Hamid; Kaihani, Sajad
Abstract The electrochemical functionalization of N, N′‐diphenylbenzene‐1, 4‐diamine with mercaptohetaromatics as electrophiles under the formation of thioethers is described.